Structured process execution middleware for Grid computing - Cicerre, F. R. L.; Madeira, E. R. M.; Buzato, L. E. (Concurrency and computation, 2006)
Grid computing is a model for wide‐area distributed and parallel computing across heterogeneous networks in multiple administrative domains. It strives to provide breakthrough computing power at low cost. Nowadays there are dozens of academic and commercial products that allow execution of isolated tasks on Grids, but few products support the coordination of long‐running processes in a distributed fashion. In order to address the subject, this paper presents a programming model and a middleware that support the hierarchical execution of structured processes using available nodes in a Grid environment. Their advantages are adaptable and structured coordination of activities, with better execution scalability, performance, reliability and easy monitoring. This paper also presents results that demonstrate the efficiency of this structured model, supporting dynamic adaptation of process execution through the use of an application that searches for prime numbers. Copyright © 2005 John Wiley & Sons, Ltd.